Jardin japonais en France : exotisme, adaptation, invention - Hiromi Matsugi (Projets de Paysage)
Through the history of the Japanese garden in France from the end of the 19th century to the beginning of the 21st century, we intend to question the evolution of the art of a foreign garden introduced in France. Appearing in France at the end of the 19th century in the World Fair and with followers of japonisme, the Japanese garden develops along its own lines in the 20th century. The 1980 and 1990 decades are those of a new expansion of the Japanese garden, influenced by diplomacy and events, but present time designers refuse to follow traditional rules and are more interested in adapting their work to local needs, and in developing new ideas. We will ask what promotes this freedom of interpretation.